STUDENTS’ NEEDS ANALYSIS IN LEARNING ENGLISH AT SMK TI ANNAJIYAH BAHRUL ‘ULUM - Diana, Ilvi Nur (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2023)
Need analysis has an important role in designing English course at tertiary education level. This study aims to determine vocational high school students’ needs at SMK TI ANNAJIYAH Bahrul ‘Ulum in learning English, including target needs, learning needs, and the most dominant needs. Descriptive qualitative method used in this study by share the questionnaire to 36 twelve grade students and interviewing the English teacher. The finding of this study show that 18 students (50%) learn english to support their future career. Speaking skill is seen as the most needed skill to master by 22 students (61%). This result corroborated by teacher’s statement which emphasize speaking skill as the most important English skill for students. 15 students (41,7%) stated that the most motivating learning activity is the question and answer method about relevant topics and issues. From this result, concluded that speaking skill need to be prioritized through learning activity in the form of discussing topics or issues related to the skills of Vocational High School students namely Software Engineering (RPL) and multimedia in English learning for twelve grade students at SMK TI ANNAJIYAH Bahrul ‘Ulum.